Fluorodeoxyglucose uptake is associated with low tumor-infiltrating lymphocyte levels in patients with small cell lung cancer. (August 2019) - Kasahara, Norimitsu; Kaira, Kyoichi; Yamaguchi, Koichi; Masubuchi, Hiroaki; Tsurumaki, Hiroaki; Hara, Kenichiro; Koga, Yasuhiko; Sakurai, Reiko; Higuchi, Tetsuya; Handa, Tadashi; Oyama, Tetsunari; Yokobori, Takehiko; et al.
Highlights: The relationship between the SCLC immune environment and 18 F-FDG uptake is unclear. We investigated tumor immunity in SCLC patients who underwent 18 F-FDG PET. 18 F-FDG uptake was higher in patients with low CD4(+) and CD8(+) TILs. High 18 F-FDG uptake predicted shorter survival, especially with limited disease. Abstract: Objectives: Positron emission tomography (PET) using 2-deoxy-2-[ 18 F] fluoro-D-glucose ( 18 F-FDG) is a clinically useful modality for cancer evaluation. The mechanism of 18 F-FDG uptake within cancer cells involves the glucose transporter 1 (GLUT1) and hypoxia-inducible factor-1 α (HIF-1α). Although recent research has shown its clinical efficacy in small-cell lung cancer (SCLC), no suitable biomarker has been identified. We conducted a clinicopathological study to examine the relationship between tumor immunity and 18 F-FDG uptake in patients with SCLC. Materials and methods: Tumor sections were stained by immunohistochemistry for GLUT1, HIF-1α, PD-L1, CD4, CD8, and Foxp3. The relationship between clinicopathological features and 18 F-FDG uptake was analyzed. Student's t -test, χ2 test, non-parametric Spearman's rank test, and Kaplan–Meier method were used to evaluate associations between the variables. Results: A total of 98 patients 78 men and 20 women who underwent 18 F-FDG PET, were enrolled in this study. PD-L1 was expressed in 36.7% (36/98) of all patients; this was significantly associated with GLUT1 expression (p = 0.04). The accumulation of 18 F-FDG was significantly higher in patients with low CD8 and CD4 TILs than in those with high TILs (p = 0.03 and p = 0.01, respectively). The uptake of 18 F-FDG was not significantly associated with the expression of either Foxp3 or PD-L1. Multivariate analysis demonstrated that advanced stage, poor ECOG-PS, and high SUVmax were independent predictors of poor OS. Among patients with limited-stage disease, multivariate analysis confirmed high PD-L1 expression and a high SUVmax to be independent predictors of poor OS. However, only ECOG-PS was found to be an independent predictor of poor OS among patients with extensive-stage tumors. Conclusion: High SUVmax on 18 F-FDG-PET is correlated with low expression of CD8(+) and CD4(+) TILs, but is an independent prognostic factor for OS, particularly in those with limited disease. Further studies are warranted to validate our findings.